การพัฒนารูปแบบการพัฒนาศักยภาพองค์การของเทศบาลเมืองคูคต - กาฬวงศ์, สืบวงศ์; โลทะกะ, สุภารมย์; แช่มจะโปะ, พินิจ; แช่มจะโปะ, พินิจ; พันธุ์ไทย, เกรียงไกรยศ; เพ็ชรอาภรณ์, สันติเลิศ (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2018)
The purpose of this research is composed of four objectives which are 1). examine the organizational competency in Khukhot municipality 2). explore the problems that affected to the organization and 3). develop the organizational competency model for Khukhot municipality. This research uses a mixed method which is included Participatory Action Research (PAR) approach, documentary research, and quantitative method. A study of 711 populations was divided into three groups which are 1). executive officers in Khukhot municipalities, 2). officers in Khukhot municipalities, and 3). residents in Khukhot municipality. The study applied various data collection instruments including interviews, focus group, observations, and muestionnaire. The descriptive statistic tool was for analyzing quantitative data while the combination between analytic induction and topology approach were for analyzing qualitative data. The finding reveals that developing a model of organizational competency in KhuKhot municipality consists of three domains. First, Khukhot municipality organizational competencies are considered by three attributes. To begin with, individual competencies. Next, the organizational culture. Last, communication that builds people’s trust. In overall, the organizational competencies and organizational culture of Khukhot municipality are at a high level while communication attribute is at a moderate level. Second, the organizational competency in Khukhot municipality is comprised of five issues, namely, sensing of the unfairness evaluation system in an organization, employee learning and responsibility problems addressing by job design, compromising strategy to avoid an internal conflict, and unclear organizational development goal. Third, a competency development model for Khukhot municipality is suggested to be focused on 1). a review of assessment system 2). ownership embodies of the community by enhancing their roles in communication process 3). adaptability and competency-based approach to job design 4). a clear goal in organizational development and 5). an adjustment in strategic planning of Khukhot municipality.